Destructive quantum interference in heterocyclic alkanes: the search for ultra-short molecular insulators. Issue 30 (7th July 2021) - Zhang, Boyuan; Garner, Marc H.; Li, Liang; Campos, Luis M.; Solomon, Gemma C.; Venkataraman, Latha
Abstract : We present a combined experimental and theoretical study of small saturated heterocyclic alkanes and show that they perform well as insulators with an electronic transmission that is suppressed due to destructive interference. Abstract : Designing highly insulating sub-nanometer molecules is difficult because tunneling conductance increases exponentially with decreasing molecular length. This challenge is further enhanced by the fact that most molecules cannot achieve full conductance suppression with destructive quantum interference. Here, we present results for a series of small saturated heterocyclic alkanes where we show that conductance is suppressed due to destructive interference. Using the STM-BJ technique and density functional theory calculations, we confirm that their single-molecule junction conductance is lower than analogous alkanes of similar length. We rationalize the suppression of conductance in the junctions through analysis of the computed ballistic current density. We find there are highly symmetric ring currents, which reverse direction at the antiresonance in the Landauer transmission near the Fermi energy. This pattern has not been seen in earlier studies of larger bicyclic systems exhibiting interference effects and constitutes clear-cut evidence of destructive σ-interference. The finding of heterocyclic alkanes with destructive quantum interference charts a pathway for chemical design of short molecular insulators using organic molecules.